Efficient oxygen storage property of Sr–Fe mixed oxide as automotive catalyst support. Issue 3 (14th November 2018) - Beppu, Kosuke; Hosokawa, Saburo; Asakura, Hiroyuki; Teramura, Kentaro; Tanaka, Tsunehiro
Abstract : Pd/Sr3 (Fe0.8 Ni0.2 )2 O7− δ showed a high catalytic activity for NO reduction under a wide range of oxygen concentrations due to the excellent oxygen storage capacity. Abstract : The efficiency of catalytic systems for the removal of nitrogen oxides (NO x ) from automotive exhaust gases is strongly affected by the oxygen concentration in the exhaust gas. To overcome this problem, an oxygen storage material has been used in the purification systems. This study demonstrates the NO reduction under various oxygen concentrations over Pd/Sr3 Fe2 O7− δ catalysts in which Fe is partially replaced by other transition metals (Mn, Co, Ni, and Cu). Pd/Sr3 (Fe0.8 Ni0.2 )2 O7− δ with a layered perovskite structure showed the highest NO reduction activity among the examined catalysts under a wide range of oxygen concentrations. Ni 3+ was found to replace Fe 3+ rather than Fe 4+ in Sr3 Fe2 O7− δ . Pd/Sr3 (Fe0.8 Ni0.2 )2 O7− δ showed significantly improved oxygen storage capacity as compared to Pd/Sr3 Fe2 O7− δ, which was attributed to the redox between Ni 3+ and Ni 2+ accompanying the Fe 4+ /Fe 3+ redox reaction during oxygen release/storage processes. This study provides useful information for the design of novel catalysts with a perovskite-type structure.